Unveiling Pelvic Organ Pathologies: A Laparoscopic Exploration of Female Infertility at a Tertiary Care Hospital: Unveiling Pelvic Organ Pathologies: A Laparoscopic Exploration of Female Infertility - Jabeen, Saima; Tahir, Shabnam; Quraish, Fozia Umber; Hafiz, Haiqa; Nasir, Inshaal; Ali, Tayyaba Nusrat; Sikandar, Mirza Zeeshan (Pakistan Journal of Health Sciences, 2025)
The World Health Organization (WHO) estimates the global prevalence of infertility at 17.5% with little discrimination among regions, lifetime prevalence coming to 17.8% in high-income countries and 16.5% in low- and middle-income countries. In Pakistan, no large-scale multicenter studies have been conducted to assess the prevalence of infertility. The United Nations Population Fund (UNFPA) estimated it to be around 22% in 2003. No studies other than small-scale cross-sectional studies have been done. Objective: To investigate the causes of unexplained infertility in Pakistani women undergoing diagnostic laparoscopy. Methods: A cross-sectional study was conducted at Shalamar Medical College and Teaching Hospital from October 2023 to June 2024. All patients >18 years of age, who had a complete infertility workup (ultrasonography (USG), endocrine markers and male partner semen analysis negative or equivocal, resulting in no diagnosis, were included in this study. Results: Primary infertility (73%) was more frequent than secondary infertility (27%). The most common diagnoses for primary infertility were polycystic ovaries (22%) and endometriosis (16.4%). Tubal blockages (52.5%) were the most frequent tubal pathology. Laparoscopy confirmed the diagnosis of unexplained infertility and provided valuable information for treatment planning. Conclusions: This study suggests a high prevalence of primary infertility with delayed diagnosis in Pakistan. Traditional delays in seeking treatment and limited access to laparoscopy highlight the need for improvement in infertility care. Laparoscopy provides a panoramic and magnified view of the pelvic organs. It is a reliable tool to identify the causes of infertility that are usually missed on a non-invasive work-up.